(untitled) (Моделювання, керування та інформаційні технології, 2025)
The article is devoted to the study of ecological wars as one of the main modern global environmental challenges to humanity. Interest in the problem of ecological warfare is due to the significant influence of natural factors on the economic component of states. Analysing ecological warfare through the characteristic features of modern global environmental challenges to humanity, theoretical conclusions are confirmed by practical examples from the world history of South Vietnam, Yugoslavia, Kuwait, Azerbaijan and Ukraine. The author analyses the concept of ‘ecological warfare’ and distinguishes it from other similar concepts. The author’s concept of ecological warfare, which should be understood as a set of actions, measures taken by adversaries in the course of a protracted in time with a certain intensity of armed conflict, the parties of which as the main (or predominant) means use the destruction (significant destruction) of the environment, the consequence of which can become an ecological disaster. Of particular interest is the conclusion that the consequence of environmental warfare is an ecological catastrophe that can jeopardise the existence of humankind.